Impact of Sports-Related Subconcussive Injuries in Soccer Players - Díaz-Rodríguez, Yarimar I.; Salvatore, Anthony P. (Seminars in Speech and Language, 2019)
Sports-related subconcussive impacts to the head are receiving increased interest. Recent evidence indicates that subconcussive impacts will have greater relevance across time because of the number of repetitive impacts. Soccer players are at risk of receiving at least one impact during a soccer game. The authors review the cognitive-communication functioning following subconcussive head injuries in youth and recommendations for baseline assessments and cognitive-communication dysfunctions after subconcussive impacts in youth. The review is followed by a description and discussion of a study that assessed the cognitive-communicative dysfunction in young soccer players prior to and following a series of soccer matches and recommendations for monitoring recovery of cognitive-communication.
Keywords: subconcussive impacts; neurocognitive assessment; pediatrics; adolescent; adult; mTBI